KELAM VE İSLAM FELSEFESİ ETKİLEŞİMİ BAĞLAMINDA NASÎRÜDDİN TÛSÎ'NİN MÜCERRET AKIL YORUMU. - YURTKURAN, Muhammet (Dinbilimleri Journal)
The article examines Nasir al-Din Tusi’s interpretation of the abstract intellect in the context of the interaction between Islamic theology (kalam) and philosophy. While Tusi accepts the existence of the abstract intellect as the necessary locus of the "commanding self" (nafs al-amr), which is the epistemological foundation of knowledge and truth, he rejects the hierarchy of multiple intellects based on the emanation theory of the Islamic Peripatetic philosophers; instead, he develops a singular model of the abstract intellect grounded in God’s absolute will and direct creation. In this model, the abstract intellect is positioned not as an ontological necessity but as a possible and eternal being; the idea of necessary intermediary beings between God and the world is criticized and rejected. Furthermore, Tusi argues that the multiplicity in the abstract intellect arises not from individual entities but from the diversity of universal concepts contained within the intellect. As a result, Tusi’s approach presents an original and coherent metaphysical framework within Islamic thought by reinterpreting philosophical concepts in light of theological principles.